Beyond play: The interplay of analogy and enjoyment in game-based learning - Sittichai Wichaidit; Patcharee R. Wichaidit (Journal of Pedagogical Research, 2024)
Game-based learning has gained significant attention from educational researchers because of its ability to create an engaging and enjoyable learning environment for students. However, there was a research gap regarding the design of game mechanics that specifically helped students understand abstract scientific concepts. Also, the impact of increased motivation, interest, and engagement on conceptual understanding remained uncertain. The objective of this study was, therefore, to analyze the efficacy of using analogy teaching as a learning design principle for creating game mechanics to improve students' conceptions of bioaccumulation and biomagnification. Additionally, the study aimed to investigate whether providing a clear analogy comparison after gameplay could have a significant impact on students' learning outcomes. The research also examined the correlation between students' enjoyment level during gameplay and their learning outcomes. An embedded experimental mixed methods design was utilized to address the research objectives. The participants were 54 undergraduate students from non-science disciplines. They were divided into two groups: the Game-based Learning [GL] group and the Game-based Learning with eXplicit analogy discussion [GLX] group. Both groups used a board game to learn about bioaccumulation and biomagnification. The GL group had reflective discussions about the concepts after playing the game. The GLX group had an additional task where they identified similarities and differences between the gameplay and the scientific concepts, and they explicitly discussed these through a worksheet provided before the discussion. Results showed that after engaging in game-based learning, both groups exhibited a significant improvement in their understanding of bioaccumulation and biomagnification, moving from incomplete or partial understanding to more scientifically accurate concepts. Notably, the GLX group scored higher in post-tests compared to the GL group. Despite high levels of enjoyment during gameplay, there was no correlation between this enjoyment and the post-test scores. An unexpected slight negative correlation was found between immersion during the game and post-test scores. Discussion and implementation of the research results were provided.